2004
DOI: 10.1207/s15327736me1704_3
|View full text |Cite
|
Sign up to set email alerts
|

Market Competition and the Media Performance of Taiwan's Cable Television Industry

Abstract: Using industrial organization as the theoretical framework, this study examines the relation between market competition and the media performance of Taiwan's cable television industry. The media performance of cable television systems is defined as the subscribers' satisfaction with program service, customer service, and community service. A telephone survey was conducted to collect data for the study. This study's findings in general support a positive relation between market competition and media performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…Therefore, evaluations of the performance of a cable television system should concern not only the products Downloaded by [Mount Allison University 0Libraries] at 05:58 06 October 2014 it provides, but also the services offered to its subscribers and to the community (C. Y. Chen, 1999;Chipty, 2001;Jacobs, 1995;Li, 2004).…”
Section: Media Performance Of Cable Television Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, evaluations of the performance of a cable television system should concern not only the products Downloaded by [Mount Allison University 0Libraries] at 05:58 06 October 2014 it provides, but also the services offered to its subscribers and to the community (C. Y. Chen, 1999;Chipty, 2001;Jacobs, 1995;Li, 2004).…”
Section: Media Performance Of Cable Television Systemsmentioning
confidence: 99%
“…With more franchise areas exhibiting a monopolistic market structure, scholars are becoming increasingly concerned with the performance of cable television system operators in Taiwan. Li (2004), in a study on this issue, found a positive relation between market competition and the media performance of Taiwan's cable television industry. However, Li (2004) employed only one dimension to measure the media performance; namely, the subscribers' satisfaction with program service, customer service, and community service.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The extant literature on industry convergence generally uses concept frameworks and case studies [15][16][17], although a few quantitative investigations have focused on measuring industry convergence [2,18]. The perspective of an industry platform is useful to understand firm conduct in a converging industry [19,20], while the traditional theoretical framework of industrial organization enables analysis of firm conduct in industries where market boundaries are clear [21]. With this theoretical perspective, the paper analyzes two potential industry platforms in China's converging video industry, i.e., OTT (over the top) service providers and cable operators.…”
Section: Introductionmentioning
confidence: 99%